2014
DOI: 10.1371/journal.pone.0090775
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor-Like Leg Movements Evoked by Rhythmic Arm Movements in Humans

Abstract: Motion of the upper limbs is often coupled to that of the lower limbs in human bipedal locomotion. It is unclear, however, whether the functional coupling between upper and lower limbs is bi-directional, i.e. whether arm movements can affect the lumbosacral locomotor circuitry. Here we tested the effects of voluntary rhythmic arm movements on the lower limbs. Participants lay horizontally on their side with each leg suspended in an unloading exoskeleton. They moved their arms on an overhead treadmill as if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 68 publications
6
47
0
Order By: Relevance
“…2a, 2b, 6a, 6b). These results, like the data obtained by other authors [12,18,23,24], show the activation of coupling between the cervical and lumbosacral levels of regulation of upper and lower limb movements depending on both central com mands and intersegmental interactions. In passive movements, the influence of central commands is sup posed to be weaker [25], whereas peripheral feedback coupled with limb movements is similar during passive and active arm movements [28,29].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2a, 2b, 6a, 6b). These results, like the data obtained by other authors [12,18,23,24], show the activation of coupling between the cervical and lumbosacral levels of regulation of upper and lower limb movements depending on both central com mands and intersegmental interactions. In passive movements, the influence of central commands is sup posed to be weaker [25], whereas peripheral feedback coupled with limb movements is similar during passive and active arm movements [28,29].…”
Section: Discussionsupporting
confidence: 90%
“…It may be suggested that what occurs on the interneurons of the lumbar spinal cord is inte gration of the proprioceptive inputs from moving arms and vibrated leg muscles, which even under the sub threshold vibration conditions, promotes in the acti vation of stepping automatism. The effect obtained can be compared with the influence of stepping arm movements on the activation of the leg central pattern generator reported by Sylos Labini et al [23]. How ever, in this study, the proprioceptive inflow from mov ing arms was substantially stronger as the arms moved with the treadmill band support.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The maximum muscle activation value obtained in each of the three attempts was used to calculate the MVC. Also, EMG envelopes were assumed to be zero if the maximum value was less than 3 lV, which was considered to be the noise level (Solopova et al, 2011a,b;Sylos-Labini et al, 2014). These data were exported as text data into a custom-written Microsoft Excel program to determine the metric for measuring muscle activation: the ratio of muscle activation during steppinglike movements on the tilt table to that at the normal grade of MMT (% MVC).…”
Section: Surface Electromyography Analysismentioning
confidence: 99%
“…Both CPGs display facilitatory interlimb neural coupling via propriospinal connections, as in quadrupedal animals . Importantly, voluntary rhythmic arm movements increase leg muscle recruitment during submaximal recumbent stepping , modulate leg muscle activity during standing , and can even evoke stepping‐like leg movements . Solopova et al have shown that peripheral sensory stimulation (continuous muscle vibration) and central tonic activation (postcontraction state of neuronal networks following a long‐lasting isometric voluntary effort, that is, Kohnstamm phenomenon) can evoke nonvoluntary rhythmic arm movements in human subjects, but also nonvoluntary rhythmic arm movements together with rhythmic movements of legs.…”
Section: Targeting Central Pattern Generatorsmentioning
confidence: 99%